SOS-associated division inhibition gene sfiC is part of excisable element e14 in Escherichia coli. - Maguin, E (1986)
The cell division inhibition gene sfiC and the excisable element e14, both associated with the SOS response in Escherichia coli, are located at 25 min on the E. coli map. Blotting with a fragment of e14 DNA showed a strict correlation between the presence of e14 and the sfiC+ genotype. Introduction of only e14 into a recA- sfiC- strain made the strain sfiC+. These results show that the sfiC gene is part of e14.